Case report: Cor pulmonale in COPD - Amin, Muhamad Shodiqul; Hendriyanto, Pujo (Science Midwifery, 2024)
Cor Pulmonale is a condition of altered function and structure of the right ventricle of the heart caused by respiratory disease, mainly due to Chronic Obstructive Pulmonary Disease (COPD). This disease results in increased blood flow resistance in the pulmonary circulation and can lead to right heart failure. A 64-year-old man came to the emergency room with complaints of worsening shortness of breath accompanied by a cough with phlegm, leg edema, and a history of COPD. Physical and laboratory examination revealed cardiomegaly, aortic elongation, and right pleural effusion. The patient was diagnosed with COPD-induced cor pulmonale. Cor pulmonale is closely related to pulmonary hypertension caused by COPD. Chronic hypoxia and other factors such as chronic hypercapnia and anatomical disturbances in the pulmonary vasculature are the main causes of this condition. Diagnosis is made through clinical examination, echocardiography, and CT scan. Treatment involves pharmacological therapy that aims to reduce symptoms and improve respiratory function. Cor pulmonale is a serious condition often caused by COPD. Proper treatment and early diagnosis are essential to prevent further complications.